Sistem Pendukung Keputusan Pemilihan Reseller Terbaik Menggunakan TOPSIS - Agung Deni Wahyudi (CV. Keranjang Teknologi Media, 2024)
The selection of the best reseller is a crucial aspect in a company's distribution strategy. This process involves a careful assessment of a number of criteria, including previous sales performance, reputation, financial capability, geographic location, and quality of customer service. The problem in choosing the best reseller is that there is no system used in determining the best reseller, even though there are criteria used in determining the best reseller. This study aims to select the best resellers by applying a decision support system model using the TOPSIS method, so that it can help companies determine the best resellers who will help the sustainability of the company's sales performance. The ranking results of the best resellers based on the TOPSIS method show rank 1 with a final value of 0.5845 obtained by Reseller E, rank 2 with a final value of 0.5838 obtained by Reseller G, and rank 3 with a final value of 0.5612 obtained by Reseller J. The ranking of the best resellers not only provides an in-depth view of the performance of business partners, but also becomes a foundation for companies to optimize distribution strategies and increase market share.